Analysis of Students' Critical Thinking Skills on the Topic of Electromagnetic Induction - Nurani Fitri; Parno; Nuril Munfaridah; Nina Diana Nawi (Postgraduate, University of Mataram, 2025)
Electromagnetic induction is one of the physics topics that is considered difficult. Research shows that students' critical thinking skills on this topic are weak. This study aims to determine the profile of high school students' critical thinking skills on this topic. The research method used is non-experimental quantitative descriptive research with a descriptive research form. Data were collected using essay test. The research sample was 22 students in 12th grade who had studied the topic of electromagnetic induction in one of the high schools in East Java, Indonesia. The sampling technique used is convenience sampling. The instrument used is in the form of a test named electromagnetic induction critical thinking skills instrument. Data were analysed using descriptive statistics. The results of the study showed that students' critical thinking skills are relatively low. Therefore, in learning, methods, models, and media are needed to help students improve their critical thinking skills.